2013
DOI: 10.1016/j.pain.2013.03.036
|View full text |Cite
|
Sign up to set email alerts
|

Naturalistic parental pain management during immunizations during the first year of life: Observational norms from the OUCH cohort

Abstract: No research to date has descriptively catalogued what parents of healthy infants are naturalistically doing to manage their infant's pain over immunization appointments during the first year of life. This knowledge, in conjunction with an understanding of the relationships different parental techniques have with infant pain-related distress, would be useful when attempting to target parental pain management strategies in the infant immunization context. This study presents descriptive information about the pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 41 publications
7
55
0
Order By: Relevance
“…It is however possible that the pain control measures apparent during vaccinations as seen in the posted videos are not representative of all vaccinations, as the act of videotaping precludes holding the infant, breastfeeding or administering sucrose unless a tripod or third party is available to operate the camera. However, the observed infrequent use of recommended pain management strategies are concordant with results of published surveys of health care professionals’ pain management practices during immunization [4,7,25,26] as well as a recent observational study of pain management practices in infants during immunization [38]. This highlights that, so far, current evidence and guidelines relating to pain management strategies, most of which has been available prior to the date of the first YouTube posting, have been unsuccessful in changing immunization pain practices.…”
Section: Discussionsupporting
confidence: 81%
“…It is however possible that the pain control measures apparent during vaccinations as seen in the posted videos are not representative of all vaccinations, as the act of videotaping precludes holding the infant, breastfeeding or administering sucrose unless a tripod or third party is available to operate the camera. However, the observed infrequent use of recommended pain management strategies are concordant with results of published surveys of health care professionals’ pain management practices during immunization [4,7,25,26] as well as a recent observational study of pain management practices in infants during immunization [38]. This highlights that, so far, current evidence and guidelines relating to pain management strategies, most of which has been available prior to the date of the first YouTube posting, have been unsuccessful in changing immunization pain practices.…”
Section: Discussionsupporting
confidence: 81%
“…There was also weak concurrent validity between the 3-item NFCS pain scores and MAISD caregiver behaviours (physical comfort, rocking and verbal reassurance). In line with previous research by Lisi et al [22], again using the same dataset but the full 7-item version of the scale, small positive associations were found between pain scores and caregiver behaviours. The magnitude of relationships between NFCS and caregiver behaviours were similar for both the seven-and three-item versions of NFCS.…”
Section: Concurrent Validity Of Nfcs With Caregiver Behaviourssupporting
confidence: 91%
“…were included in the current analyses, as they have been shown to have the strongest relationship with infant pain-related distress [6,22]. The three caregiver behaviours were coded as present (1) or absent (0) for five-second epochs during the following three 60-second periods: (1) the oneminute period prior to the needle, (2) the one-minute period following the last needle, and (3) the two-minute period following the last needle.…”
Section: Measure Of Adult and Infant Soothing And Distress (Maisd) Imentioning
confidence: 99%
See 1 more Smart Citation
“…The first infant waves of the cohort were naturalistic observations of infants and their parents at their 2, 4, 6 and 12 month immunizations. Among the findings from this longitudinal study, it was found that commonly occurring parent pain management strategies from the literature (e.g., rocking, proximal soothing, verbal reassurance) accounted for statistically significant yet minimal amounts of variance in infant pain responding (ranging from 2 to 13%) [5][6][7]. It was shown that as children aged over the first year of life, parent strategies accounted for increasing variance in observed childhood pain-related distress.…”
Section: Parent-led Interventions Have Minimal Effect On Infant Pain mentioning
confidence: 71%